Packaging method and application of laminated solar cell

In the packaging of stacked solar cells, glass powder liquid and laser pulse technology are used to form a package structure with a reserved inflation hole, which solves the problems of optical loss and poor sealing in the prior art, and achieves higher stability and photoelectric conversion efficiency.

CN119604159AActive Publication Date: 2025-03-11华能青海发电有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411694617.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the packaging technology of existing laminated solar cells, high-temperature lamination, ultraviolet light and other processes will damage the battery performance, and the inorganic thin film layer is slowly packaged and costly, resulting in optical loss and poor sealing problems.

Method used

Glass powder liquid is laid around the effective area of ​​the battery between the front plate glass and the back plate glass, and laser pulse scanning is used to melt and solidify the glass powder liquid, forming a packaging structure with a vent hole reserved, and then air is extracted through the vent hole and filled with inert gas and secondary laser irradiation is performed to achieve sealing.

Benefits of technology

It improves water and oxygen barrier properties, reduces optical losses, reduces edge dead zone area, and improves the stability and photoelectric conversion efficiency of stacked batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604159A_ABST
    Figure CN119604159A_ABST
Patent Text Reader

Abstract

The invention discloses a packaging method and application of a laminated solar cell. According to the invention, the glass powder is laid around the battery effective area between the front plate glass and the back plate glass, the glass powder is melted and solidified by laser pulse irradiation to form the packaging structure with the reserved inflation hole, the inert gas is filled after air extraction through the inflation hole, and secondary laser irradiation is carried out to prevent water vapor from entering, so that the finished packaging structure is formed. The water and oxygen barrier property is improved, the optical loss is reduced, the edge dead zone area is reduced, and the stability and the photoelectric conversion efficiency of the laminated cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cell packaging, and in particular to a packaging method and application of a laminated solar cell. Background Art

[0002] At present, the packaging technology of stacked solar cells mainly uses organic polymer materials for packaging or depositing inorganic thin film layers on the surface of the cells for packaging. When using organic polymer materials for packaging, high temperature lamination and ultraviolet light used in the process will damage the performance of the cells and cause optical losses; when depositing inorganic thin film layers on the surface of the cells for packaging, the packaging speed is slow and the cost is high. Therefore, it is necessary to propose a packaging method for stacked solar cells to reduce optical losses. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0004] To this end, an embodiment of the present invention provides a packaging method and application of a stacked solar cell.

[0005] In a first aspect, the present invention provides a packaging method for a stacked solar cell, such as Figure 1 As shown, the following steps are included:

[0006] (a) Laying the top cell on the front glass plate and installing bus bars on both sides of the top cell;

[0007] (b) After installing the busbar on the bottom cell, lay it on the back glass, and lay the adhesive film and non-stick film on the surface in sequence, and peel off the non-stick film after lamination;

[0008] (c) printing and laying glass powder liquid around the active area of ​​the top cell, wherein the glass powder liquid is printed on the surface and both sides of the bus bar in the portion with the bus bar, and is printed on the front glass in the portion without the bus bar;

[0009] (d) After the busbar of the top battery is led out from the wiring hole of the bottom battery, the top battery and the bottom battery are stacked, and the inflation hole is reserved, and laser pulse scanning is performed;

[0010] (e) After the air is evacuated from the inflation hole, an inert gas is filled in to maintain the pressure at one atmosphere, and the inflation hole is scanned with a laser pulse to achieve complete sealing.

[0011] Among them, the front glass is the light-receiving surface, the back glass is the backlight surface, and the effective area of ​​the top battery refers to the power generation area.

[0012] Furthermore, the printed width of the glass powder liquid is greater than the width of the bus bar, and the sum of the thickness of the bus bar and the thickness of the glass powder liquid printed on the surface thereof is equal to the thickness of the glass powder liquid printed on the front plate glass.

[0013] In the present invention, the printing width of the glass powder liquid is greater than the width of the bus bar, so that the glass powder liquid completely covers the bus bar where the bus bar is present, thereby avoiding incomplete sealing at the bus bar and preventing water vapor from entering. The sum of the thickness of the bus bar and the thickness of the glass powder liquid printed on the surface thereof is equal to the thickness of the glass powder liquid printed on the front plate glass, so that the overall thickness of the glass powder is consistent, thereby avoiding poor sealing caused by uneven thickness of the glass powder.

[0014] Furthermore, the thickness of the printed glass powder liquid is 0.7-3.2 mm. In the actual printing process, the printing thickness of the glass powder liquid is designed according to specific working conditions.

[0015] Furthermore, the glass powder liquid is obtained by dispersing glass powder in diethylene glycol butyl ether acetate, the median particle size of the glass powder is 10 to 30 μm, and the melting point of the glass powder is 400 to 500°C.

[0016] The glass powder is evenly dispersed in diethylene glycol butyl ether acetate to form a glass powder liquid. The main component of the glass powder is silicon oxide. The median particle size of the glass powder is 10 to 30 μm. Too large or too small a particle size of the glass powder is not conducive to packaging.

[0017] Furthermore, the wavelength of the laser pulse is one of 355 nm, 532 nm, and 1064 nm, and the pulse width of the laser pulse is 10 -10 ~10 -15 s, single pulse energy is 1~500μJ, and scanning speed is 1~500mm / s.

[0018] Compared with continuous laser, the photothermal effect of pulsed laser is weaker, which can avoid laser damage to the component film layer and busbar welding.

[0019] Furthermore, the width of the inflation hole is 5 to 10 mm.

[0020] Furthermore, the top cell is a perovskite cell, and the bottom cell is one of a crystalline silicon cell, a perovskite cell, and an organic cell.

[0021] Furthermore, the inert gas is high-purity nitrogen or argon.

[0022] Furthermore, the wiring hole is opened on the back panel glass.

[0023] In a second aspect, the present invention proposes the application of the packaging method proposed in the first aspect in the packaging of laminated solar cells.

[0024] Compared with the prior art, the beneficial effects of the present invention are:

[0025] The present invention lays glass powder around the effective area of ​​the battery between the front glass and the back glass, uses laser pulse irradiation to melt and solidify the glass powder to form a packaging structure with reserved air holes, evacuates air through the air holes, fills with inert gas and performs secondary laser irradiation to prevent water vapor from entering, thereby forming a complete packaging structure, improving the water and oxygen barrier, reducing optical loss, reducing the edge dead zone area, and improving the stability of the laminated battery and the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0027] Figure 1 This is a flow chart of the packaging method of the stacked solar cell of the present invention;

[0028] Figure 2 This is a schematic diagram of the packaging structure of a stacked solar cell according to Embodiment 1 of the present invention;

[0029] Figure 3 The efficiency attenuation curves of Example 1, Comparative Example 1 and Comparative Example 2 are shown;

[0030] Description of reference numerals:

[0031] 1 Wiring hole; 21 front glass, 22 back glass; 3 complete packaging structure; 4 bus bar; 5 glass powder liquid; 61 top battery, 62 bottom battery; 7 filling hole. DETAILED DESCRIPTION

[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0033] The present invention is specifically described below in conjunction with embodiments.

[0034] Example 1

[0035] (1) Figure 2 As shown, the top battery 61 is laid on the front glass 21. The top battery 61 is a perovskite battery. The glass size is 400mm×400mm, the effective area size is 366mm×366mm, the band gap is about 1.65eV, and bus bars 4 are welded on both sides of the battery. The width of the bus bar is 3mm and the thickness is 0.5mm.

[0036] (2) The bottom cell 62 is a crystalline silicon cell, which is composed of 4 pieces of 182perc cells. After being serially welded and the bus bar 4 is welded, it is laid on the back glass 22, and a glue film and a non-stick film are laid on its surface in turn. After being placed in a laminator for lamination, the non-stick film is peeled off. The width of the bus bar is 3 mm and the thickness is 0.5 mm.

[0037] (3) Print and lay glass powder liquid 5 around the effective area of ​​the top battery 61. In the part with busbars, it is printed on the surface and both sides of the busbars. The width of the glass powder liquid at the busbars is 3.2mm and the thickness is 2mm. In the part without busbars, it is printed on the surface of the front plate glass 21. The width of the glass powder liquid is 3.2mm and the thickness is 2.5mm. The melting point of the glass powder is about 450℃, the median particle size of the glass powder is 15μm, and the main component of the glass powder is silicon oxide.

[0038] (4) After the busbar of the top battery 61 is led out from the wiring hole 1 of the bottom battery 62, the top battery 61 and the bottom battery 62 are superimposed and a 355 nm laser (pulse width: 10 -10 seconds; single pulse energy: 200μJ; scanning speed: 20mm / s) is scanned clockwise from the left side of the reserved filling hole 7 to the right side to melt the glass powder, and after solidification, a packaging structure with a reserved filling hole is formed, and the width of the reserved filling hole is 8mm.

[0039] (5) After the air is evacuated through the air filling hole 7, high-purity nitrogen is introduced and the pressure is maintained at one atmosphere. A 355 nm laser (pulse width: 10 -10 seconds; single pulse energy: 200 μJ; scanning speed: 20 mm / s) scans the filling hole, so that the glass powder at the filling hole melts and solidifies to form a complete packaging structure 3.

[0040] Example 2

[0041] (1) The top cell 61 is laid on the front glass 21. The top cell 61 is a perovskite cell. The glass size is 400mm×400mm, the effective area size is 366mm×366mm, the band gap is about 1.65eV, and bus bars 4 are welded on both sides of the cell. The width of the bus bar is 3mm and the thickness is 0.5mm.

[0042] (2) The bottom cell 62 is a crystalline silicon cell, which is composed of 4 pieces of 182perc cells. After being serially welded and the bus bar 4 is welded, it is laid on the back glass 22, and a glue film and a non-stick film are laid on its surface in turn. After being placed in a laminator for lamination, the non-stick film is peeled off. The width of the bus bar is 3 mm and the thickness is 0.5 mm.

[0043] (3) Print and lay glass powder liquid 5 around the effective area of ​​the top battery 61. In the part with busbars, it is printed on the surface and both sides of the busbars. The width of the glass powder liquid at the busbars is 3.4mm and the thickness is 2mm. In the part without busbars, it is printed on the surface of the front plate glass 21. The width of the glass powder liquid is 3.4mm and the thickness is 2.5mm. The melting point of the glass powder is about 450℃, the median particle size of the glass powder is 15μm, and the main component of the glass powder is silicon oxide.

[0044] (4) After the busbar of the top battery 61 is led out from the wiring hole 1 of the bottom battery 62, the top battery 61 and the bottom battery 62 are superimposed and a 355 nm laser (pulse width: 10 -10 seconds; single pulse energy: 200μJ; scanning speed: 20mm / s) is scanned clockwise from the left side of the reserved filling hole 7 to the right side to melt the glass powder, and after solidification, a packaging structure with a reserved filling hole is formed, and the width of the reserved filling hole is 8mm.

[0045] Example 3

[0046] (1) The top cell 61 is laid on the front glass 21. The top cell 61 is a perovskite cell. The glass size is 400mm×400mm, the effective area size is 366mm×366mm, the band gap is about 1.65eV, and bus bars 4 are welded on both sides of the cell. The width of the bus bar is 3mm and the thickness is 0.5mm.

[0047] (2) The bottom cell 62 is a crystalline silicon cell, which is composed of 4 pieces of 182perc cells. After being serially welded and the bus bar 4 is welded, it is laid on the back glass 22, and a glue film and a non-stick film are laid on its surface in turn. After being placed in a laminator for lamination, the non-stick film is peeled off. The width of the bus bar is 3 mm and the thickness is 0.5 mm.

[0048] (3) Print and lay glass powder liquid 5 around the effective area of ​​the top battery 61. In the part with busbars, it is printed on the surface and both sides of the busbars. The width of the glass powder liquid at the busbars is 3.6mm and the thickness is 2.5mm. In the part without busbars, it is printed on the surface of the front plate glass 21. The width of the glass powder liquid is 3.6mm and the thickness is 3mm. The melting point of the glass powder is about 450℃, the median particle size of the glass powder is 15μm, and the main component of the glass powder is silicon oxide.

[0049] (4) After the busbar of the top battery 61 is led out from the wiring hole 1 of the bottom battery 62, the top battery 61 and the bottom battery 62 are superimposed and a 355 nm laser (pulse width: 10 -10seconds; single pulse energy: 200μJ; scanning speed: 20mm / s) is scanned clockwise from the left side of the reserved filling hole 7 to the right side to melt the glass powder, and after solidification, a packaging structure with a reserved filling hole is formed, and the width of the reserved filling hole is 8mm.

[0050] Comparative Example 1

[0051] (1) The top cell is a perovskite cell with a glass size of 400 mm × 400 mm, an active area size of 366 mm × 366 mm, a band gap of approximately 1.65 eV, and bus bars welded on both sides of the cell, where the width of the bus bar is 3 mm and the thickness is 0.5 mm.

[0052] (2) The bottom cell is a crystalline silicon cell, which is composed of 4 182perc cells. After being serially welded and the bus bar is welded, it is laid on the back glass. The bus bar is 3mm wide and 0.5mm thick.

[0053] (3) Lay a film on the surface of the effective area of ​​the bottom battery, lay a 10 mm wide butyl rubber on the edge of the glass, lead the top battery bus bar out from the wiring hole of the bottom battery, and then stack the top battery and the bottom battery for lamination packaging.

[0054] Comparative Example 2

[0055] (1) The top cell is a perovskite cell with a glass size of 400 mm × 400 mm, an active area size of 366 mm × 366 mm, a band gap of approximately 1.65 eV, and bus bars welded on both sides of the cell. The width of the bus bars is 3 mm and the thickness is 0.5 mm.

[0056] (2) The bottom cell is a crystalline silicon cell, consisting of 4 pieces of 182perc cells. After being serially soldered and the busbars are welded, they are laid on the back glass. The surface is successively covered with adhesive film and non-stick film. After being placed in a laminator for lamination, the non-stick film is peeled off. The width of the busbar is 3 mm and the thickness is 0.5 mm.

[0057] (3) Print and lay glass powder liquid around the effective area of ​​the top battery. In the part with busbars, it is printed on the surface and both sides of the busbars. The width of the glass powder liquid at the busbars is 3.2mm and the thickness is 2mm. In the part without busbars, it is printed on the surface of the front plate glass. The width of the glass powder liquid is 3.2mm and the thickness is 2.5mm. The melting point of the glass powder is about 450℃, the median particle size of the glass powder is 15μm, and the main component of the glass powder is silicon oxide.

[0058] (4) After the top cell busbar is led out from the wiring hole of the bottom cell, the top cell and the bottom cell are stacked and a 355 nm laser (pulse width: 10 -10seconds; single pulse energy: 200 μJ; scanning speed: 20 mm / s) scans clockwise along the glass powder laying area to form a packaging structure with reserved filling holes.

[0059] Test Example 1

[0060] The components prepared in Example 1 and Comparative Examples 1 and 2 were subjected to an efficiency attenuation test under the double 85 condition. The efficiency attenuation curves are shown in FIG. Figure 2 shown.

[0061] from Figure 2 It can be seen that the efficiency retention rate of Example 1 is better than that of Comparative Examples 1 and 2. The efficiency of Example 1 decays by 3% after 1000 hours of testing. Comparative Example 1 adopts the traditional edge sealing method of adhesive film plus butyl adhesive, and the efficiency decays by 12% after 1000 hours of testing. Comparative Example 2 only performs laser packaging once, and the efficiency decays by 70% after 500 hours of testing. The reason is that water vapor enters the interior of the component, causing the component efficiency to decay faster.

[0062] Test Example 2

[0063] The photoelectric conversion efficiency and electrical performance tests were performed on Example 1, Comparative Example 1 and Comparative Example 2. The test results are shown in Table 1.

[0064]

[0065]

[0066] It can be seen from Table 1 that the photoelectric conversion efficiency of Examples 1 to 3 of the present invention is better than that of Comparative Examples 1 and 2.

[0067] According to the above, the present invention lays glass powder around the effective area of ​​the battery between the front glass and the back glass, uses laser pulse irradiation to melt and solidify the glass powder to form a packaging structure with reserved filling holes, evacuates the air through the filling holes, fills with inert gas and performs secondary laser irradiation to prevent water vapor from entering, thereby forming a complete packaging structure, improving the water and oxygen barrier, reducing optical losses, reducing the edge dead zone area, and improving the stability of the stacked battery and the photoelectric conversion efficiency.

[0068] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0069] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0070] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A packaging method for a laminated solar cell, characterized in that: The following steps are involved: (a) Laying the top cell on the front glass plate and installing bus bars on both sides of the top cell; (b) After installing the busbar on the bottom cell, lay it on the back glass, and lay the adhesive film and non-stick film on the surface in sequence, and peel off the non-stick film after lamination; (c) printing and laying glass powder liquid around the active area of ​​the top cell, wherein the glass powder liquid is printed on the surface and both sides of the bus bar in the portion with the bus bar, and is printed on the front glass in the portion without the bus bar; (d) After the busbar of the top battery is led out from the wiring hole of the bottom battery, the top battery and the bottom battery are stacked, and the inflation hole is reserved, and laser pulse scanning is performed; (e) After the air is evacuated from the inflation hole, an inert gas is filled in to maintain the pressure at one atmosphere, and the inflation hole is scanned with a laser pulse to achieve complete sealing.

2. The packaging method according to claim 1, characterized in that: The printed width of the glass powder liquid is greater than the width of the bus bar, and the sum of the thickness of the bus bar and the thickness of the glass powder liquid printed on the surface thereof is equal to the thickness of the glass powder liquid printed on the front plate glass.

3. The packaging method according to claim 2, characterized in that: The thickness of the printed and laid glass powder liquid is 0.7 to 3.2 mm.

4. The packaging method according to claim 2, characterized in that: The glass powder liquid is obtained by dispersing glass powder in diethylene glycol butyl ether acetate, the median particle size of the glass powder is 10 to 30 μm, and the melting point of the glass powder is 400 to 500° C.

5. The packaging method according to claim 1, characterized in that: The wavelength of the laser pulse is one of 355nm, 532nm, and 1064nm, and the pulse width of the laser pulse is 10 -10 ~10 -15 s, single pulse energy is 1~500μJ, and scanning speed is 1~500mm / s.

6. The packaging method according to claim 1, characterized in that: The width of the inflation hole is 5 to 10 mm.

7. The packaging method according to claim 1, characterized in that: The top cell is a perovskite cell, and the bottom cell is one of a crystalline silicon cell, a perovskite cell, and an organic cell.

8. The packaging method according to claim 1, characterized in that: The inert gas is high-purity nitrogen or argon.

9. The packaging method according to claim 1, characterized in that: The wiring hole is opened on the back panel glass.

10. Use of the packaging method according to any one of claims 1 to 9 in packaging of laminated solar cells.

Citation Information

Patent Citations

  • Solar energy cell packaging method

    CN102231407A

  • Film solar cell component and packaging method thereof

    CN103681918A

  • Photovoltaic module and packaging method thereof

    CN112038431A

  • Laser powder sintering and laser welding combined packaging method for perovskite solar cell

    CN116322218A